Thermal biology of Liolaemus lizards from the high Andes: Being efficient despite adversity - Valdecantos, Maria Soledad (2013)
We studied the efficiency of thermoregulation in four high elevation Liolaemus species in the Andes of Salta, Argentina; L. irregularis, L. multicolor, L. albiceps and L. yanalcu. One of the species, L. irregularis, shows a broad distribution being in allopatry in some localities and in sympatry with L. albiceps, L. multicolor and L. yanalcu at different sites. Together with this variation in assemblages, the degree of phylogenetic relatedness is different with L. irregularis being most closely related to L. albiceps than to the other two species (L. multicolor and L. yanalcu). We measured body (Tb), microenvironmental (Ta, Ts), and operative temperatures (Te) in the field, and preferred body temperature (Tpref) in laboratory for each one of the species of assemblages. Three out of the four species showed a high thermoregulatory efficiency except for L. yanalcu, a moderate thermoregulator. The species studied here show high Tb in the field compared to most of the recorded Liolaemus species. However, the Tpref values were similar to other Liolaemus species. No evidence of thermal niche segregation between species in sympatry was observed. Our results suggest that the species studied here, despite of living at high elevation and harsh climatic conditions are able to behaviorally or physiologically thermoregulate to achieve Tbs close to their Tpref, probably because of low predation risk and perhaps low levels of competition.